The Infrared Spectroscopy Applied to Determine the Volume Fraction of Ethyl Alcohol in Alcohol-Containing Liquids - V. M. Bulanov; I. L. Kazantseva (Теория и практика судебной экспертизы)
The article addresses the capacity of infrared spectroscopy to determine the strength of alcoholcontaining liquids. The method is based on calculating the ratio of optical densities of the characteristic bands of alcohol and water (D1045/D1650) and determining the volume fraction of ethyl alcohol in the liquid according to the calibration graph plotted in advance. The proposed method does not require sample preparation. It allows us to work with a small volume of the investigated liquid when it is impossible to use standard methods for determining the volume fraction of ethyl alcohol (pycnometric, areometric). Infrared spectra are registered on the equipment typical for forensic institutions of the Ministry of Justice of Russia – an IR-Fourier spectrometer using an attachment for liquid samples or an IR-spectrometer with impaired total internal reflection attachment. The proposed method for determining the strength of alcohol-containing liquids is also suitable for liquids containing flavoring agents and coloring substances and does not require preliminary sample preparation such as distillation. The inaccuracy of determination of ethyl alcohol’s volume fraction in a liquid by the proposed method is ± 5 % rel.